KARAKTERISTIK KEBULATAN TERHADAP PARAMETER PROSES PEMBUBUTAN PADA MATERIAL ST 42 MENGGUNAKAN METODE TAGUCHI DAN ANOVA - Hendri Van Hoten; Rijalul Rahman Hakim; Helmizar Helmizar; Nurbaiti Nurbaiti (ROTOR, 2021)
This research is about the roundness characteristics of the turning process parameters on St 42 material using the Taguchi and ANOVA (Analysis of Variance) methods. A cylindrical product requires a good roundness value to ensure its quality. One of the factors that determine the quality of these products is the machining process parameters. In this study, optimization of the turning process parameters using the Taguchi and ANOVA methods was carried out on the roundness characteristics of the workpiece. The workpiece used is Steel St 42. The lathe used is the Krisbow Precision Gear Head Machine 410X1000MM. After data analysis using the Taguchi method, the parameters with the optimum roundness value of 7.385 µm were 510 rpm spindle rotation, 1mm depth of cut, and coolant opening valve. The results of the ANOVA analysis show the percent contribution of each parameter, respectively, as follows: spindle rotation 26.97%, depth of cut 24.82%, and coolant 38.63%.